The intonation of information-seeking absolute interrogatives in Madrid Spanish - Gorka Elordieta; Magdalena Romera (Estudios de Fonética Experimental)
Romera and Elordieta (2019) and Elordieta and Romera (2020) reported that most information-seeking absolute interrogatives in the variety of Spanish spoken in the Basque Country have a rising-falling circumflex final contour. Basque has falling final contours in absolute interrogatives. Applying the same methodology, this paper shows that most information-seeking absolute interrogatives in Madrid Spanish end in a high rising configuration. The results of this research strengthen the hypothesis proposed by Romera and Elordieta (2019) and Elordieta and Romera (2020) that the variety of Spanish spoken in the Basque Country shows influence from Basque.